2021
DOI: 10.1002/elsa.202000037
|View full text |Cite
|
Sign up to set email alerts
|

Biomass derived hierarchically porous carbon inherent structure as an effective metal free cathode for Li‐O2/air battery

Abstract: A hierarchical porous carbon framework derived from betel-nut is synthesized and employed as a bifunctional cathode in a Li-O 2 /air battery. The prepared betel nut derived activated porous carbon (BNAPC) material exhibits an ordered and merged tube-like porous morphology and a high specific surface area of 768 m 2 /g. The presence of both meso and micro porous leads to a well-developed 3D interconnected carbon framework, which provides an efficient path for the diffusion of the reactant (oxygen as well as air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…It has been demonstrated that the side products and corrosion during the ORR/OER process are the main reasons for the degradation of carbon-based catalysts in LOBs. [17,52,55] It can be concluded that the surface phosphatization can efficiently prevent the corrosion and the formation of side products of carbon-based catalysts in LOBs. This can be attributed to the catalytic capability of the P-doped active sites discussed in the following theoretical section.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the side products and corrosion during the ORR/OER process are the main reasons for the degradation of carbon-based catalysts in LOBs. [17,52,55] It can be concluded that the surface phosphatization can efficiently prevent the corrosion and the formation of side products of carbon-based catalysts in LOBs. This can be attributed to the catalytic capability of the P-doped active sites discussed in the following theoretical section.…”
Section: Resultsmentioning
confidence: 99%
“…The twin problems of the energy crisis and environmental pollution have been the most serious challenges for the development of the global community in recent years. The main focus of research and development is on seeking a combination of theoretical research and experimentation to address these two major challenges, thereby realizing a new generation of more environmentally friendly energy technologies [ 1 , 2 , 3 , 4 ]. One focus is on the conversion and storage of clean energy, while lithium-ion battery (LIB) systems are one of the most anticipated energy storage devices [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, substantial efforts were devoted to design appropriate host materials and structures with both high electrical conductivity and excellent mechanical flexibility, such as conductive polymers [14,15], graphene [16,17], carbon nanotubes [18], and some metal oxides and sulfides [19][20][21]. Recently, as a viable and effective alternative, biomass-derived carbon materials were widely developed for both Li-S batteries and other metal-ion batteries because of their sustainability, easy availability, low-cost, and environmental friendliness [22][23][24][25]. For example, Guo et al prepared porous Fe 7 S 8 nanowires on a SiO x /nitrogen carbon matrix by hydrothermal reaction and the calcination of bamboo leaves.…”
Section: Introductionmentioning
confidence: 99%